2002
DOI: 10.1016/s0951-8320(01)00095-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrating objective and subjective hazard risk in decision-aiding system design

Abstract: A generalized model is presented to incorporate objective (hard) and subjective (soft) hazard information in automated decision-aiding systems. The model may be used with more than one hazard, of more than one type, in a given problem. Uncertainties in state measurements, dynamics, hazard extent, and hazard severity are included, as is consideration of the fact that different operators may have different concepts of what is an acceptable or unacceptable risk. By examining the tradeoffs created by these uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…22 In particular, the previous data during landing are employed to further optimize the landing risk model. Kuchar et al 23 regard the risk as the operational constraint conditions in the decision-aiding system, which is an innovation idea. However, the studies above do not consider the future landing states and the subjective feeling of the pilots.…”
Section: Introductionmentioning
confidence: 99%
“…22 In particular, the previous data during landing are employed to further optimize the landing risk model. Kuchar et al 23 regard the risk as the operational constraint conditions in the decision-aiding system, which is an innovation idea. However, the studies above do not consider the future landing states and the subjective feeling of the pilots.…”
Section: Introductionmentioning
confidence: 99%
“…S EVERAL efforts in air traffic management research propose methods for constructing decision-support tools to increase the safety and efficiency of the air traffic control (ATC) system. As Kuchar et al [1] have noted, these tools will be accepted by the operators of the ATC system only if they are "aligned with operator mental models". Currently, understanding of how the risks created by thunderstorm activity are evaluated and how mitigation strategies are chosen by pilots and ATC system operators is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Radar reflectivity and VIL measures were shown to be relevant to classification. Kuchar et al [1] studied a similar data set, taken during 12 h of operations at the Dallas-Fort-Worth TRACON and focusing on 353 penetration trajectories. The authors found that all aircraft avoided VIL level 6 activity, but that as VIL levels decreased, gradually more aircraft flew through storm activity for extended periods of time.…”
Section: Introductionmentioning
confidence: 99%